Finance, trade, and politics in British foreign policy 1815-1914 - Platt, D. C. M. (Oxford ; London : Clarendon P., 1968)
This book deals with finance, trade, and polities in British foreign policy
Include index
Bibliography: p. [418]-433.
oo 11/10/18
Loans
Keywords: Great Britain; Great Britain; Great Britain